Reducing intervention- and research-induced inequalities to tackle the digital divide in health promotion - Laura M. König; Rebecca A. Krukowski; Emmanuel Kuntsche; Heide Busse; Laura Gumbert; Kathrin Gemesi; Efrat Neter; Nor Firdous Mohamed; Kathryn M. Ross; Yetunde O. John-Akinola; Rosie Cooper; Anila Allmeta; et al. (International Journal for Equity in Health, 2023)
Abstract Social inequalities are an important contributor to the global burden of disease within and between countries. Using digital technology in health promotion and healthcare is seen by some as a potential lever to reduce these inequalities; however, research suggests that digital technology risks re-enacting or evening widening disparities. Most research on this digital health divide focuses on a small number of social inequality indicators and stems from Western, educated, industrialized, rich, and democratic (WEIRD) countries. There is a need for systematic, international, and interdisciplinary contextualized research on the impact of social inequality indicators in digital health as well as the underlying mechanisms of this digital divide across the globe to reduce health disparities. In June 2023, eighteen multi-disciplinary researchers representing thirteen countries from six continents came together to discuss current issues in the field of digital health promotion and healthcare contributing to the digital divide. Ways that current practices in research contribute to the digital health divide were explored, including intervention development, testing, and implementation. Based on the dialogue, we provide suggestions for overcoming barriers and improving practices across disciplines, countries, and sectors. The research community must actively advocate for system-level changes regarding policy and research to reduce the digital divide and so improve digital health for all.